External validation of the quick Sequential Organ Failure Assessment score for mortality and bacteraemia risk evaluation in Japanese patients undergoing haemodialysis: a retrospective multicentre cohort study. Issue 7 (11th July 2019) - Nishiwaki, Hiroki; Sasaki, Sho; Hasegawa, Takeshi; Sasai, Fumihiko; Kawarazaki, Hiroo; Minatoguchi, Shun; Uchida, Daisuke; Koitabashi, Kenichiro; Ozeki, Takaya; Koiwa, Fumihiko
Abstract : Objectives: We aimed to examine the validity of the quick Sequential Organ Failure Assessment (qSOFA) score for mortality and bacteraemia risk assessment in Japanese haemodialysis patients. Design: This is a retrospective multicentre cohort study. Setting: The six participating hospitals are tertiary-care institutions that receive patients on an emergency basis and provide primary, secondary and tertiary care. The other participating hospital is a secondary-care institution that receives patients on an emergency basis and provides both primary and secondary care. Participants: This study included haemodialysis outpatients admitted for bacteraemia suspicion, who had blood drawn for cultures within 48 hours of their initial admission. Primary and secondary outcome measures: The primary outcome measure was overall in-hospital mortality. Secondary outcomes included 28-day in-hospital mortality and the incidence of bacteraemia diagnosed based on blood culture findings. The discrimination, calibration and test performance of the qSOFA score were assessed. Missing data were handled using multiple imputation. Results: Among the 507 haemodialysis patients admitted with bacteraemia suspicion between August 2011 and July 2013, the overall in-hospital mortality was 14.6% (74/507), the 28-day in-hospital mortality was 11.1% (56/507) and the incidence of bacteraemia, defined as a positive blood culture, was 13.4% (68/507). For predicting in-hospital mortality among haemodialysis patients, the area under the receiver operating characteristic curve was 0.61 (95% CI 0.56–0.67) for a qSOFA score ≥2. The Hosmer-Lemeshow χ 2 statistics for the qSOFA score as a predictor of overall and 28-day in-hospital mortality were 5.72 (p=0.02) and 7.40 (p<0.01), respectively. Conclusion: On external validation, the qSOFA score exhibited low diagnostic accuracy and miscalibration for in-hospital mortality and bacteraemia among haemodialysis patients.